EXAMINATION OF LABOR MARKET PROBLEMSIN THE CONDITIONS OF GLOBALIZATION - OSIPOVA, L. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The main form of development of the country’s labor potential is the labor market, in which the main actors are employers and workers. The national labor market is the most important part of the country’s economy, which has characteristics and has a specific model of functioning. At the same time, globalization has a significant impact on the development of the national labor market and, as a consequence, on the formation and realization of the country’s labor potential and the position of workers and employers. In today’s global economy, the labor market is changing rapidly. Deep demographic changes, military-political conflicts, introduction of technological innovations (production automation, robotics, three-dimensional printing, digital technologies, etc.), global outsourcing change the spheres of employment of different countries. Those countries that are aware of these trends in time and successfully adapt to the challenges of the times will not only be able to solve pressing labor market problems, but also provide a foundation for increasing the efficiency of the national economy, increasing labor productivity, improving quality of life and more. The article describes what is the globalization of the labor market. The main reasons for the process of globalization of the labor market are highlighted. The key changes that have a direct impact on the state of the labor market are considered. The dynamics of the economically active population for the last ten years is shown and analyzed. The key problems of employment in Ukraine have been identified. Peculiarities of aggravation of labor market problems in the conditions of globalization are considered. It is proved that a bright indicator of the labor market in the context of globalization is unemployment, which has become quite common for Ukraine. An analysis of the dynamics of unemployment in Ukraine and in some countries around the world over the past nine years. It is shown that the level of wages is the main factor determining the situation in the labor market. The level of wages in certain sectors of the national economy is analyzed, the highest and lowest levels are determined. Possible ways to solve labor market problems in the context of globalization are outlined.